Developments Of Methods In Production Of Sugars From Cassava - Ho, Wei Yen (Universiti Malaysia Sarawak (UNIMAS), 2009)
Cassava (Manihot esculent a) is a starchy plant material which can be hydrolyzed to produce reducing sugars with the help of bacterial enzymes and subsequently can be fermented to produce ethanol. Enzymatic hydrolysis was carried out in 2 stages namely liquefaction and saccharification with the help of enzymes, Termamyl 120-L and Dextrozyme under optimum condition. Three samples SOOg of cassava pulps were added with SOOml, 1000ml and ISOOml distilled water. Then, the starch content, dry matter and moisture content were determined. The highest starch content was from the sample SOOg + SOOml that has starch content of 72.3 giL. There was a 72.7 giL of glucose being produced indicating a 100.6 % glucose recovery. Batch fermentation was conducted for 24 hours using shake flask but the pH was uncontrolled where Baker's yeast or Saccharomyces cerevisae was used. Initial pH was set at pH S.S, temperature 34°C and agitation rate of ISO rpm. There was 100 % ofglucose consumption where 11.24 giL ethanol was produced from 26.93 giL ofglucose. Thus, the fermentation efficiency was recorded 81.04 % in this study with dry cell weight of 1.96 giL. In conclusion, hydrolyzed raw cassava starch is a suitable substrate for hydrolysis to produce reducing sugars which can be fermented into ethanol under batch fermentation.